Preparation of core–shell WC-Co composite powder. (August 2014) - Li, Y.; Xie, K.; Ye, J.; Meng, Z.; Liao, L.
<x content-type="archive" xml:space="preserve">Abstract</x> An effective route to prepare core–shell WC-Co composite powder by a liquid phase chemical reduction was proposed. The core–shell structure that Co layer was coated on the surface of WC particles was confirmed by the characterisation results. The microstructure and properties of the sintered cemented carbide bulk were also investigated and characterised. The resultant bulk exhibits homogeneous and fine grain microstructure, as well as the good combined mechanical properties.